Decomposing differences in health and inequality using quasi-objective health indices - Dörte Heger (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
People in Canada and the U.S. often make claims regarding whose country has a better health system. Several researchers have attempted to address this question by analysing subjective health in the two countries, thus assuming a common definition of 'good' health. Using data from the Joint Canada/U.S. Survey of Health, I generate quasi-objective health indices and show that Canadians and Americans define 'good' health differently. After controlling for reporting heterogeneity, health differences between Americans and Canadians are eliminated for intermediate health statuses, while health differences at the tails of the health distribution lead to slightly better average population health in Canada. In both countries, income and education gradients increase steeply with poor health. – – Es wird häufig debattiert, ob das kanadische oder das amerikanische Gesundheitssystem vorzuziehen ist. Um diese Frage zu beantworten, haben Forscher die subjektive Gesundheit in Kanada und den USA verglichen, was eine Übereinstimmung in der Definition von "guter Gesundheit' in beiden Ländern voraussetzt. Anhand von Daten des Joint Canada/U.S. Survey of Health konstruiere ich zwei quasi-objektive Gesundheitsindizes und zeige, dass diese Bedingung für Kanadier und Amerikaner nicht erfüllt ist. Berücksichtigt man die Heterogenität im Antwortverhalten, verschwinden Unterschiede im Gesundheitszustand zwischen Amerikanern und Kanadiern weitgehend. Verbleibende Unterschiede am unteren und oberen Rand der Gesundheitsverteilung führen zu einem leicht besseren durchschnittlichen Gesundheitszustand in Kanada. In beiden Ländern steigt der Einkommens- und Bildungsgradient mit schlechtem Gesundheitszustand deutlich.
Keywords: C43; I13; I14; I18; 330; Public health; inequality; Oaxaca-Blinder decomposition